Revision of Madeiran mayflies (Insecta, Ephemeroptera) - Gattolliat, Jean-Luc; Hughes, Samantha J.; Monaghan, Michael T.; Sartori, Michel (Zootaxa, 2008)
A comprehensive revision of the mayflies (Ephemeroptera) inhabiting the island of Madeira (Portugal) is presented, based on newly collected specimens and DNA sequence analysis. Disregarding a report of a single Centroptilum female subimago that is very likely a misidentification, the Madeira mayfly fauna encompasses three species, all belonging to the Baetidae. Previous reports of the continental species Cloeon dipterum Linnaeus, 1758 are erroneous, as all examined specimens belong to the new species Cloeon peregrinator n.sp. Gattolliat and Sartori. Baetis atlanticus Soldán & Godunko, 2006 is by far the most common and abundant species on the island. A second new species, B. enigmaticus n.sp. Gattolliat and Sartori is established for larvae presenting rheophilous adaptations similar to those of B. pseudorhodani Müller-Liebenau, 1971 from the Canary Islands.